The theology of Amos Yong and the new face of Pentecostal scholarship : passion for the spirit - Vondey, Wolfgang.; Mittelstadt, Martin William. (Global Pentecostal and Charismatic Studies, 2013)
In The Theology of Amos Yong and the New Face of Pentecostal Scholarship , Wolfgang Vondey and Martin William Mittelstadt gather a table of experts on one of the most influential voices in current Pentecostal theology. The authors provide an introduction and critical assessment of Yong's biblical foundations, hermeneutics, epistemology, philosophical presuppositions, trinitarian theology, theology of religions, ecumenical and interfaith relations, theology of disability, engagement with contemporary culture, and participation in the theology and science conversation. These diverse topics are pursued through the complementary perspectives that together shape Yong's methodology: pneumatology, pentecostalism, and the possibility of renewal. The contributors invite a more thorough reading of Yong's work and propose a more substantial engagement with the new face of Pentecostal scholarship. Contributors include Andrew Carver, Jacob D. Dodson, Jeff Hittenberger, Mark Mann, Martin William Mittelstadt, L. William Oliverio, Jr., David A. Reed, Tony Richie, Christopher A. Stephenson, Steven M. Studebaker, Paraskevè (Eve) Tibbs, and Wolfgang Vondey.